A szövegalapú "társadalomtudomány" lehetőségei - Pászka Imre (Bölcsészműhely, 2007)
By combining elements of German hermeneutics, French structuralism as well as English speech act theories, Paul Ricoeur intends to restore the harmony of content and form. Nonetheless, connecting hermeneutics and speech act theory tackles only the explanation/interpretation of the meaning of the text. His attempt to favour the concept of explanation over interpretation is not convincing. The reason is that it is impossible to interpret without explanation and argumentation — this requires no structuralist algebra. By rehabilitating the hermeneutical cycle Ricoeur designates the subject of social sciences in the texts to archive and precludes oral forms. Such a one-sidedness is somewhat odd, since every oral utterance is recorded, and in the final analysis, the subject of social sciences is constituted through written texts. The major virtue of Ricoeur's theory is the actualization of the unity of textually-based social sciences.